Stürze und Sturzrisikofaktoren: von Bedeutung in der ambulanten HNO-Versorgung? - Walther, Leif Erik; Kleeberg, Jürgen; Hörmann, Karl (HNO, 2012)
Background and objectiveThe risk of falling increases with age. The problem of falls in medical care constantly rises in priority due to demographic changes in Germany. Therefore, the risk of falling should be assessed in all patients. The present study was intended to evaluate the frequency of falls in daily ENT outpatient medical care and the importance of risk factors.Patients/methodsA multicentre study was performed in six outpatient facilities based on a survey of falls and fall risk factors in patients living at home (n = 673) aged 60 years and older.ResultsFalls are a frequent problem in the elderly. A total of 23% had one and 13.7% more than one fall within the previous year. Of these, 15% suffered injury, while only 13% used some form of fall prevention. Joint pain and problems of the hip and lower extremities (42.6%), abnormal gait (41.3%), dizziness and balance disorders (38%) as well as impaired activities of daily living (35%) are the most common risk factors for falls and multiple falls in all age groups. Impaired hearing is a fall risk factor in elderly patients.ConclusionsFalls are a frequent problem in patients in ENT outpatient medical care. Fall prevention is advisable in the context of an interdisciplinary approach.